Occupational injuries and psychological support in Chinese nurses: a cross-sectional study - Wenyu Zhang; Zixuan Yan; Xueli Zhang; Hongying Pi; Xiaoyong Sai (SciELO, 2021)
ABSTRACT Objective: To assess the occupational injuries and psychological support received by nurses and to investigate the relationship between the two. Method: This was a nation-wide cross-sectional study of nurses working across 1858 hospitals in China. Data were collected using an online structured, self-administered questionnaire between 2016 and 2017. Results: Nearly half of respondents had experienced aggressive behavior from patients or their attendants; 13.4% respondents had experienced aggressive behavior on more than three occasions. 78.96% respondents had experienced needle-stick injuries and 51.22% had experienced psychological trauma. 20.5% respondents believed that hospitals do not pay any attention to occupational safety. 86.1% respondents expressed the need for little or moderate psychological support. Nurses who had experienced aggressive behavior expressed a greater need for psychological support. Nurses working at hospitals that adequately addressed the occupational safety issues expressed the lowest need for psychological support. Conclusion: We found a high prevalence of psychological stress and occupational injuries among nurses. Nursing managers need to address this issue and implement interventions to prevent and reduce injuries.